Discordant City Employment Cycles - Michael Owyang; Jeremy Piger; Howard Wall (European Regional Science Association (ERSA), 2011)
The national economy is often described as having a business cycle over which aggregate output enters and exits distinct expansion and recession phases. Analogously, national employment cycles in and out of its own expansion and contraction phases, which are closely related to the business cycle. This paper estimates city-level employment cycles for 58 large U.S. cities and documents the substantial cross-city variation in the timing, lengths, and frequencies of their employment contractions. It also shows how the spread of city-level contractions associated with U.S. recessions has tended to follow recession-specific geographic patterns. In addition, cities within the same state or region have tended to have similar employment cycles. There is no evidence, however, that similarities in employment cycles are related to similarities in industry mix. This suggests that the U.S. employment and business cycles has a spatial dimension that is independent of broad industry-level fluctuations.
Keywords: 330